HUBUNGAN LAMA MENDERITA DENGAN KEJADIAN NEUROPATI PERIFER DIABETIK PADA WANITA USIA PRODUKTIF DI WILAYAH KERJA PUSKESMAS SERING MEDAN - Waruwu, Melvin Intan Sovia; Wahyu, Afnijar (STIKes Mitra Husada Medan, 2024)
Peripheral neuropathy in diabetes mellitus is one of the signs and symptoms of damage or dysfunction of peripheral nerves in the lower extremities due to exposure to chronic hyperglycemia. Continuously high glucose levels over a long period of up to 10 years or more will damage the walls of the capillaries that lead to the nerves. The aim of this research is to determine the relationship between long suffering and the incidence of diabetic peripheral neuropathy in women of productive age in the Medan health center work area.This research is quantitative with a cross sectional survey type of research and sampling using purposive sampling with a total sample of 38 respondents. This research uses the person product moment test to see the relationship between variables. The results of this study show that the duration of suffering, there is a significant relationship between these variables and the incidence of diabetic peripheral neuropathy with a p-value of 0.002. Conclusion: That there is a relationship between the long-suffering and the incidence of diabetic peripheral neuropathy in women of productive age in the working area of ​​the sering Medan health center. Suggestion: Future researchers are expected to carry out further research on diabetic peripheral neuropathy using other research methods such as qualitative and continuing this research by looking at the relationship between long suffering and the incidence of diabetic peripheral neuropathy with a larger sample size.